(untitled) (Research, Society and Development, 2023)
Creatine supplementation has been the subject of intense study and discussion in the context of resistance exercise. It is a topic that attracts the attention of athletes, bodybuilders and fitness enthusiasts due to its potential benefits in gaining strength and muscle mass. However, this practice is not without critical considerations. Therefore, the present research aims to: analyze the effects of creatine supplementation on resistance exercise, highlighting the benefits associated with it, as well as the possible harms that deserve attention and caution. Bibliographical study was adopted as a research method as there are numerous works published in electronic magazines, articles and books covering the same subject. And through the research carried out, it can be seen that creatine supplementation can be used on an individual approach and, preferably, under the guidance of a health professional, such as a nutritionist or sports doctor, as risks exist when the person does not uses it appropriately.